The correlation of clinical and psychological characteristics of women seeking cosmetic help - E. S. Bagnenko; E. R. Araviiskaia; A. I. Bogatenkov; S. S. Bagnenko (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Patients seeking cosmetic help, most commonly, haven`t only defects in appearance, in particular, facial skin, but also experience certain psychological problems in this regard. On the other hand, the reaction to the performed cosmetic correction of the mentioned defects depends, including on the patients psychological characteristics. The study of the correlation between clinical and psychological characteristics should contribute to the individualization of the cosmetological correction process and optimization of the patient life quality. Aims. To establish the correlation between age, clinical and psychological characteristics of women with cosmetic problems of the facial skin. Materials and methods. Using the methods of psychological diagnostics, we examined 110 women who received cosmetic assistance. Semi-quantitative method was used to assess the cosmetic problem intensity, the duration of its existence and the effect of the correction performed. Clinical and psychological research was carried out using the author's structured interview, which questions were aimed at fixing both the formal social positions of the patients and the characteristics of the system of significant relationships. Psychometric research was carried out using standardized questionnaires in order to identify a wide range of personality characteristics. In the course of statistical processing of the results, a frequency analysis of the gradations of nominative and rank signs was carried out using Pearson's 2, as well as a correlation analysis of clinical and psychological characteristics using the Spearman -test. Results. The author traced the statistical correlation between the degree of manifestation of the cosmetic problem and its influence on the psychological state of patients, as well as between the degree of their satisfaction with its solution and a number of personal characteristics and attitudes. Conclusions. The assumption was confirmed that the effect of treatment is determined not only by clinical factors and the possibilities of modern cosmetology, but also by psychological factors, among which the motivational orientation and activity of the individual, which form the basis of patient compliance, are of decisive importance.